Culture and politics - Lane, Jan-Erik; Wagschal, Uwe (Routledge, 2012)
"This concise, accessible text presents an overview of the relevance of culture for politics. Culture figures prominently in the theories of the great classics such as Marx, Durkheim and Weber. Recently, the cultural approach to politics has developed quickly, and the concept of political culture has played a role in these developments, particularly given the emergence of large-scale survey research into political value orientations. Seeking to outline this rapid development, the book is divided into three sections: Section I of the book discusses the relevance of cultural perspectives to political analysis including discussion of the most significant concepts and methods ; Section II looks at the core elements of political culture - tradition, ethnicity and religion ; Section III examines emerging research avenues and opportunities including social capital, value orientations in the postmodern world, newer formulations of political culture such as gender and sexuality and the influence of the environment. Drawing on a wealth of examples and a comprehensive analysis of comparative data, this textbook is essential reading for all students of political culture, research methods, political sociology and comparative politics."